PERAN MEDIASI QUALITY OF WORK LIFE YANG DIPENGARUHI BURNOUT TERHADAP EMPLOYEE ENGAGEMENT - Yudi Nur Supriadi; Iwan Kresna Setiadi (LP2M Universitas Bina Bangsa, 2023)
The research conducted aims to find the mediating role of quality of work life which is influenced by employee engagement. This study used a sample taken by 125 respondents from 314 populations using the calculation of the 5% slovin error sampling formula. Respondents were taken from employees of logistics services delivering goods in Tangerang City, DKI Jakarta and Depok. This research used the PLS method with the software used is SmartPLS 3.0. The results show that the burnout variable negatively affects employee engagement. The variable quality of work life positively affects employee engagement. Burnout, on the quality of work life has a positive influence. Meanwhile, the mediating role of work-life balance which is influenced by the bornout of employee engagement is 1,926 with a P value of 0.054, meaning that mediation is very low. Penliti found Novelty for this research so that bornout does not occur and can increase employee engagement with the mediation of quality of work life, namely: the company needs to increase the sense of enthusiasm at work, employees must be part of the company's strategy, must feel happy, employees are provided with the ability to do their tasks and can solve their own problems, provide programs that involve families